Quantitative and qualitative characteristics of persistence of students with different levels of progress in foreign language learning - Yu V Kozhukhova (RUDN Journal of Psychology and Pedagogics, 2011)
The article deals with the results of the quantitative and qualitative analysis of the parameters of persistence of students with different levels of progress in learning a foreign language carried out in the vein of the system-functional approach to the research of the personality.